Ocean ambient noise measurement and theory - Carey, William M. 1943-2012; Evans, Richard B. (New York, New York Springer New York, 2011)
This book develops the theory of ocean ambient noise mechanisms and measurements, and also describes general noise characteristics and computational methods.  It concisely summarizes the vast ambient noise literature using theory combined with key representative results.  The air-sea boundary interaction zone is described in terms of non-dimensional variables requisite for future experiments.  Noise field coherency, rare directional measurements, and unique basin scale computations and methods are presented.  The use of satellite measurements in these basin scale models is demonstrated.  Finally, this book provides a series of appendices giving in-depth mathematical treatments.  With its complete and careful discussions of both theory and experimental results, this book will be of the greatest interest to graduate students and active researchers working in fields related to ambient noise in the o
1: Introduction -- 2: The Air-Sea Boundary Interaction Zone -- 3: Fundamental Mechanisms -- 4: The Measurement of Oceanic Ambient Noise -- 5: Numerical Modeling of Ambient Noise -- 6: Research Issues -- Appendices -- Nomenclature -- Bibliography -- Index.
Electronic reproduction.
Keywords: Underwater acoustics